Perovskite Quantum Dot Solar Cells: An Overview of the Current Advances and Future Perspectives - Dias, Jeferson A.; Santagneli, Silvia H.; Ribeiro, Sidney J. L.; Messaddeq, Younès (Wiley, 2021)
Perovskite quantum dots (PQDs) have revolutionized the field of perovskite solar cells in recent years. Using PQDs improves the operational stability of these devices, which is one of their main drawbacks for applications. This factor has motivated an intense search for new advances, from a fundamental aspect to improved performance in devices. Therefore, the developments obtained for PQD solar cells are discussed, presenting the challenges already overcome and the upcoming tendencies for research. Thus, the fundamental aspects of halide perovskite structures are first introduced. The advantages of their preparation as quantum dots are presented as well. The advances for post-treatments (purification, passivation, and ligand exchange) are then discussed. Next, an in-depth discussion of the PQD solar cell architectures is made, highlighting both the obsolete configurations and upcoming tendencies. A more specific view of the PQD compositions is then made, including lead-free compositions and strategies for ionic substitution. Links of the photovoltaic performance are constructed with the devices’ architecture, post-treatments, and perovskite composition, providing a wide-ranging overview of these parameters for the devices’ efficiencies. Finally, the authors’ point of view about the future of PQD solar cell technology is presented, showing the main drawbacks, advantages, and opportunities for research.
Keywords: all-inorganic perovskites; ionic substitutions; lead-free perovskites; organohalide perovskites; photovoltaic performances; post-treatments; solar cell architectures